2020
DOI: 10.22555/joeed.v7i2.27
|View full text |Cite
|
Sign up to set email alerts
|

The Perceptions and Practices of University Students and Teachers about Classroom Presentations

Abstract: Students’ classroom presentations as teaching and assessment techniques are widely in practice at universities all over the world. Previous studies indicate that university students are provided unsatisfactory time for presentations. It frustrates them especially when teachers use the presentation as an assessment tool. The present study aimed to explore the views of teachers and students’ perceptions behind their dissatisfaction with the uses of presentations by teachers as a teaching method as well as an ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…The Q&A session during the presentation allowed students to share new ideas and solutions, communicate their discussion outcomes, and construct new understandings by addressing previously overlooked questions, alternative assumptions, new problem-solving strategies, and conclusions. This claim was supported by Kukul & Karataş (2019) and Kamal, et al, (2020), which suggested that presentations were crucial for boosting students' confidence in their performance. The teacher's role was facilitating dialogues that enabled students to explain their understandings using appropriate language.…”
Section: Description Of Imagistic Stages According To (Cohen and Hega...mentioning
confidence: 86%
“…The Q&A session during the presentation allowed students to share new ideas and solutions, communicate their discussion outcomes, and construct new understandings by addressing previously overlooked questions, alternative assumptions, new problem-solving strategies, and conclusions. This claim was supported by Kukul & Karataş (2019) and Kamal, et al, (2020), which suggested that presentations were crucial for boosting students' confidence in their performance. The teacher's role was facilitating dialogues that enabled students to explain their understandings using appropriate language.…”
Section: Description Of Imagistic Stages According To (Cohen and Hega...mentioning
confidence: 86%
“…Attempting to capture attention using the promised procedure before presenting the task increases the clarity of teaching behavior while also clarifying the task delivery. The clarity of task presentation has a direct effect on student and task presentation; in a well-focused state, it contributes to higher academic achievement [3,[11][12][13]. Therefore, considering students' attention is an important factor for securing and improving the clarity of task presentation, and strategic approaches toward this should be a focus of the teacher education program.…”
Section: Discussionmentioning
confidence: 99%
“…However, contrary to the expectations of teachers, the understanding level of students is not always high. The reason for this is that the teacher's task presentation may be vague, of poor quality [3], or delivering a large amount of information at once, leading to students' failing or struggling to understand the task. High-quality task presentation increases students' task adherence, practice time, and achievement [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation